i-Saraf – A web-based platform for learning Arabic morphology - Md. Noor, Mohamad Lukman Al Hakim; Abdul Aziz, Nur Farhana; Sahrir, Muhammad Sabri; Ahmad, Fauzi@Fauri (2016)
i-Saraf seeks to help students in learning Arabic morphology through the design of a computer assisted program by using multimedia via the World Wide Web. Among the factors related to this study are many students Arabic language of non-native speakers find many difficulties in learning Arab morphology, including the large number of morphological terms that lead to student psychological disorder, distraction of mind, and it becomes worst if they are presented with the views of scholar’s different views which lead them to avoid morphology subject due to its complexity and difficulty material based on learners’ perception. This study adopted two methodologies of descriptive and analytical. The researcher has collected information about the difficulties in learning Arabic morphology, theories of learning Arabic language via the World Wide Web, and designed a computer assisted program by using multimedia via the URL of http://efolio.iium.edu.my/courses/ sorof / index.html through the website of Blendspace. It was developed in the light of instructional design model of ADDIE based on the views of the respondents and their suggestions and needs. The researcher has conducted the validity and reliability check on this study among the experts in the field of teaching Arabic as a second language and educational technology. The researcher found that this multimedia learning programme is highly accepted by the respondents, as it leads to a productive and successful process of learning Arabic morphology. Keywords: Arabic morphology, multimedia learning, educational technology, instructional design, web-based learning